THE INFLUENCE OF THE YOUTUBE CHANNEL “INDONESIA FAIRY TALES” ON THE FANTASY STORY WRITING SKILLS OF GRADE VII STUDENTS OF SMP MUHAMMADIYAH 31 JAKARTA - Wahyudin, Akhmad Wahyudin; Eriyani, Reni Nur; Purbarani, Etsa (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to determine the effect of using the YouTube channel "Indonesia Fairy Tales" on the fantasy story text writing skills of seventh grade students of SMP Muhammadiyah 31 Jakarta. The method used is an experiment with a Pretest-Posttest Control Group Design. The sample was selected using simple random sampling, namely class VII-C as the experimental class and VII-D as the control class. The results of the initial and final tests showed an increase in both classes, but the increase in the experimental class was more significant (from 65 to 82), compared to the control class (from 61 to 74). The normality test with Kolmogorov-Smirnov showed that all data were normally distributed (sig. > 0.05). The homogeneity test showed that the variance between groups was homogeneous (sig. 0.121 and 0.105). The results of the hypothesis test using the t-test showed a significant difference between the experimental class and the control class (Sig. 2-tailed = 0.000 < 0.05). Thus, the use of the YouTube channel "Indonesia Fairy Tales" has been proven effective in improving students’ fantasy story text writing skills, and can be used as an alternative learning medium in Indonesian language learning